EMPORAL DISTRIBUTION, REPRODUCTIVE SYNCHRONY, AND MATING PATTERNS OF THE EXPLOSIVE BREEDER FROG DERMATONOTUS MUELLERI (ANURA: MICROHYLIDAE) - Nomura, Fausto (2022)
The knowledge about natural history of a species is fundamental for the proposition of theories in population, community, and behavioral ecology. Dermatonotus muelleri (Boettger, 1885) is one of the several Neotropical anuran species that still lacks basic information. These frogs are widely distributed in South America and present many peculiar morphological features, such as a reduced head size and a tongue morphology that suggests a specialized diet in ants and termites. In this study, we describe the reproductive ecology of D. muelleri, with special attention to the mechanisms that regulates (i) the reproductive synchrony between males and females, (ii) the operational sex ratio (OSR), and (iii) if size is a good predictor of pairs formation (assortative mating). We found that D. muelleri aggregates in short periods of reproductive activity (one to five consecutive nights) to reproduce. During the reproductive events, males and females arrive at the breeding sites in synchrony, using environmental (temperature and pluviosity) and biotic (termite reproductive swarms and male calling) cues. Also, there is a high population density (1,079 ± 816 individuals, n = 11 reproductive events), with a biased OSR toward the number of males. The intense malemale competition prevents any female choice, and the call function is related more to reduction of predation costs to females. We did not find size assortative mating in D. muelleri. The lack of size assortative mating may be a consequence of different pressure selection of males and females. While females where selected to have larger body size and offspring production, at the cost of reproductive lifespan, males are subject to an intense malemale competition which prevents the expression of female preferences.